1978
DOI: 10.1097/00005072-197807000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Immune Complex Disease: Behavioral and Immunological Correlates

Abstract: Using a fear avoidance paradigm, behavioral effects were seen in Sprague-Dawley rats in which chronic immune complex disease was induced. These effects were related to changes in urine protein that developed during the course of the experiment. Experimental animals also had glomerular deposits of rat gamma globulin and BSA as determined by immunofluorescence; C3 deposits were observed in half of these animals. BSA and/or rat gamma-globulin, but not C3, was seen in the choroid plexus of half of the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Since it is known that there are immune complex deposits in the choroid plexus of patients with SLE, as well as in animal models Hoffman et al, 1978a;Koss et al, 1973;Lampert and Oldstone, 1973;Morgan et al, 1977;Peress et al, 1977a;Peress and Tompkins, 19791, it is important to determine whether immune complexes can alter BBB permeability and in this way lead to some of the neuropsychiatric manifestations seen in this disease. It is feasible that BBB permeability changes, induced by immune complexes, could lead to altered behavior by changing cerebrospinal fluid, or extracellular fluid composition, by allowing autoantibodies or immune complexes to get into the CNS, or by making it easier for cells of the immune system to enter the CNS.…”
Section: Immune Complexes and Bbb Permeabilitymentioning
confidence: 99%
“…Since it is known that there are immune complex deposits in the choroid plexus of patients with SLE, as well as in animal models Hoffman et al, 1978a;Koss et al, 1973;Lampert and Oldstone, 1973;Morgan et al, 1977;Peress et al, 1977a;Peress and Tompkins, 19791, it is important to determine whether immune complexes can alter BBB permeability and in this way lead to some of the neuropsychiatric manifestations seen in this disease. It is feasible that BBB permeability changes, induced by immune complexes, could lead to altered behavior by changing cerebrospinal fluid, or extracellular fluid composition, by allowing autoantibodies or immune complexes to get into the CNS, or by making it easier for cells of the immune system to enter the CNS.…”
Section: Immune Complexes and Bbb Permeabilitymentioning
confidence: 99%
“…The loss of DLK abolished any response to a preconditioning injury (Figure 1). The only preconditioning effect not mimicked by DLK seems to be the shortened latency to growth cone formation, but Shin et al (2012) did not directly address whether there was a change in latency after a preconditioning injury in their experiments (Hoffman, 2010).…”
mentioning
confidence: 99%
“…Is DLK the signaling molecule responsible for the improved axon regeneration induced by a preconditioning injury? Wild-type sensory axons respond to a preconditioning injury with an accelerated regeneration after a second injury (McQuarrie and Grafstein, 1973;Hoffman, 2010). Shin et al (2012) found that this conditioning injury effect was completely abolished in DLK KO sciatic sensory axons in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations